Educational System Building. Issue 6 (September 2019) - Cohen, David K.; Spillane, James P.
Recognizing that there are many different sorts of school systems in the United States and noting the absence of comparative research on these systems, we sampled six such systems—two public, one not, and three at various places on the border between public and private—for a comparative study of educational system in the United States. In this introduction, we motivate the research and discuss our research questions in order to situated the four papers in this special issue. The first three papers capture how different systems inhabit their environments similarly and differently, exploring the relationship between environments on one hand and the system–instruction connection on the other. The fourth paper sketches a comparative research agenda that would include more school systems, in and outside the United States, as they try to improve instruction.